2017
DOI: 10.1590/1980-5918.030.001.ao04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pilates method and conversation circles on the health of older adults

Abstract: Introduction: Health education practices associated with oriented exercises have potential bene icial effect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(21 reference statements)
0
3
0
2
Order By: Relevance
“…When the second period of intervention with Pilates and the conversation circles resumed, functional autonomy improved again. Corroborating with this finding, Bertoli et al 39 showed that only 6 weeks of Pilates alone were sufficient to significantly improve all variables of functional capacity assessment. The longest study was that of Filho et al 42 , who evaluated and compared different exercise modalities, including pilates + water aerobics, for 24 weeks, and concluded that, at the end of this period, all modalities increased functional autonomy.…”
Section: Functional Autonomymentioning
confidence: 80%
See 1 more Smart Citation
“…When the second period of intervention with Pilates and the conversation circles resumed, functional autonomy improved again. Corroborating with this finding, Bertoli et al 39 showed that only 6 weeks of Pilates alone were sufficient to significantly improve all variables of functional capacity assessment. The longest study was that of Filho et al 42 , who evaluated and compared different exercise modalities, including pilates + water aerobics, for 24 weeks, and concluded that, at the end of this period, all modalities increased functional autonomy.…”
Section: Functional Autonomymentioning
confidence: 80%
“…among the nine studies [39][40][41][42][43][44][45][46][47] that assessed functional autonomy, only one 46 did not improve after the Pilates practice. The variation in the duration of the interventions was large, between 5 and 24 weeks, and it was observed that even studies with a short period of time were efficient in increasing the functional capacity.…”
Section: Functional Autonomymentioning
confidence: 99%
“…Na tentativa de aproximar os achados deste estudo com a literatura, toma-se por base estudo realizado com idosos, utilizando método Pilates e círculos de conversação, sendo que, após a intervenção, obtiveram como resultados a melhora da qualidade de vida e na queixa de dor entre os participantes de estudo 12 funcional, independência e equilíbrio emocional 13 . Esses achados tem congruência com os achados neste estudo, ao se verificar a melhoria da qualidade de vida geral dos adolescentes, porém ainda com diversos aspectos que necessitam de mais intervenções para maior impacto nas questões de vida e saúde dos adolescentes.…”
Section: Discussionunclassified
“…Gradativamente, o MP vem se mostrando eficaz na dor lombar, e, de acordo com Wells et al (2014) 12 , há um consenso total entre os fisioterapeutas em relação à indicação, aos benefícios e às precauções do método sobre a dor lombar. O estudo de Wells et al corrobora o de Duarte, Sousa e Nunes, (2017) 13 , que também encontraram benefícios do MP na condição física e de saúde, Figura 1: Fluxograma sobre metodologia da seleção dos estudos encontrados na presente pesquisa. 14 , que realizaram um estudo experimental com objetivo de verificar o efeito do Método Pilates no nível de flexibilidade de quadril e cintura escapular de idosos, notaram que, no decorrer do estudo, idosas que praticaram Pilates tiveram um aumento na flexibilidade, além de prevenir que ela piore com o avanço da idade.…”
Section: Discussionunclassified